Expansive learning among undergraduates in the social sciences in sri lanka - Wijesundera, S.; Murphy, R. (University of Jaffna, 2012)
This paper presents a model for understanding student learning in undergraduate education in the social sciences in Sri Lanka. The model is based on Cultural Historical Activity Theory and a longitudinal qualitative study conducted in a Sri Lankan University. The experiences of a group of undergraduates following a four year degree course in Psychology were studied over a 3-4 year time period using classroom observations, semi structured interviews, reflective accounts and documentary review techniques. Student learning in the undergraduate course was conceptualized as a network of interacting activity systems which weaves together people and cultural tools. In the analysis of individual differences in achieving expansive learning there emerged five interacting factors which included: a student’s past history of education; goal setting; motivation for transforming identity; mobilizing resources and views on the object and tools used in the course. These factors do not operate in isolation and they interact within an individual’s socio-cultural context of learning, which simultaneously operates with the collaborative activity of student learning in the undergraduate course. The above findings are synthesized into a model for understanding student learning in undergraduate education and the implications for practice are discussed.
Keywords: Expansive Learning; Social Sciences; Cultural Historical Activity Theory